Sociolinguistic Factors in the Development of English Language Proficiency Among Students in Malaysia - Melvina Melvina (Universitas Lancang Kuning, 2015)
Sociolinguistics factors influence the level of English Language proficiency among Malaysian students. Thereare three contextual factors involved which are the participants, the environment and culture. Participants refer to the students who come from different backgrounds with diverse needs and goals of learning the language. Language distance, native language proficiency, prior knowledge of the second language, dialect and register language status and attitudes play a crucial role in this factor. Besides that, the participants’ integrative and instrumental motivations are also contributing factors to the different level of proficiency in second language acquisition. The second factors is the environment which includes home support, the school environment and the community. Home support is concerned with atmosphere that parents create at home regarding language use, the school environment refers to peer groups, teachers and the learningprocess, whereas the community deals with the society that the students interact with. Finally cultural factors such as cultural differences and settings also have brought the different levels of proficiency among students in Malaysia.